Aerodynamic design of high-sided coaches to reduce cross-wind sensitivity, based on wind tunnel tests - Petzäll, J.; Torlund, P.; Falkmer, Torbjorn; Albertsson, P.; Björnstig, U. (Taylor and Francis Ltd., 2008)
Aerodynamic properties of high-sided coaches with various body shapes were investigated in order to improve directional stability. The idea was to find out whether it would be possible, from an aerodynamic point of view, to suggest an optimal coach body design. The subject has previously been paid little attention in the scientific literature. The fact that during the last few years at least 10 wind-related coach crashes have occurred in Sweden indicates that here a serious problem exists and that cross-wind effects should be carefully considered by coach designers. The observations made in the present study suggest that it should be possible to find an ideal coach body shape. The ideal shape of the coach includes a rounded front face, rounded top sides and sharp rear corners. Copyright © 2008 Taylor & Francis.